2014
DOI: 10.1139/cjfas-2013-0556
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile green sturgeon (Acipenser medirostris) and white sturgeon (Acipenser transmontanus) behavior near water-diversion fish screens: experiments in a laboratory swimming flume

Abstract: Water diversions that extract fresh water for urban, industrial, and agricultural uses, as well as export to southern California, are prevalent throughout the Sacramento–San Joaquin watershed. Many water diversions are fitted with fish-exclusion screens designed to prevent fish from entrainment (i.e., being drawn in). The impact of fish screens on the behavior of migrating juvenile fishes remains largely unknown, especially for threatened species such as sturgeon. We placed individual juvenile green (Acipenser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…Due to current and projected food web alterations and temperature increase in the SFBD, investigating the effects of feed restriction on whole-organism upper thermal tolerance (measured as CTMax) and the temperature sensitivity of the heat shock response (measured as Hsc/Hsp70 protein levels) of green and white sturgeon is necessary to determine how changes in food availability might influence physiological performance of each sturgeon species when faced with increased temperature. Similar to previous studies reporting species-specific differences in sensitivity to chemical contaminants (Lee et al, 2011(Lee et al, , 2012De Riu et al, 2014) and changes in water velocities near water-diversion fish screens (Poletto et al, 2014), green sturgeon may also be less tolerant than white sturgeon to temperature stress when food is limited. As a result, concurrent environmental alterations including increasing temperature and reduced food availability driven by anthropogenic activities may have a relatively larger impact on resilience of the threatened green sturgeon.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Due to current and projected food web alterations and temperature increase in the SFBD, investigating the effects of feed restriction on whole-organism upper thermal tolerance (measured as CTMax) and the temperature sensitivity of the heat shock response (measured as Hsc/Hsp70 protein levels) of green and white sturgeon is necessary to determine how changes in food availability might influence physiological performance of each sturgeon species when faced with increased temperature. Similar to previous studies reporting species-specific differences in sensitivity to chemical contaminants (Lee et al, 2011(Lee et al, , 2012De Riu et al, 2014) and changes in water velocities near water-diversion fish screens (Poletto et al, 2014), green sturgeon may also be less tolerant than white sturgeon to temperature stress when food is limited. As a result, concurrent environmental alterations including increasing temperature and reduced food availability driven by anthropogenic activities may have a relatively larger impact on resilience of the threatened green sturgeon.…”
Section: Resultssupporting
confidence: 83%
“…Comparative studies of white and green sturgeon from our group have shown that these species differ significantly in their sensitivity to chemical contaminants such as mercury and selenium (Lee et al, 2011(Lee et al, , 2012De Riu et al, 2014), to salinity challenges Lee et al, 2015) and show behavioral differences to variable water velocities around waterdiversions (e.g., Poletto et al, 2014). Taken together, results from these studies demonstrate that green sturgeon in general are more sensitive to environmental change than white sturgeon and therefore white sturgeon serve as a poor surrogate species for green sturgeon when it comes to understanding stress tolerance, effects of food limitation, and overall vulnerability to GCC.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of storage and downstream diversion, in combination, complicate the resultant ecology of the Sacramento River by adding and then subtracting substantial amounts of water exclusively within the spawning habitat we documented. Additionally, a multitude of unscreened diversions in the lower 225 rkm of the river likely negatively affect larval and juvenile habitat and survival (Mussen et al 2014;Poletto et al 2014;Verhille et al 2014).…”
Section: Water Resource Management and Competing Needs Of Esa-listed mentioning
confidence: 99%
“…Notably, the demand for water diversions increases the risk to fishes of entrainment through these structures and/or impingement on their debris racks (Barnthouse, ; Pracheil, Derolph, Schramm, & Bevelhimer, ), either of which can result in injury or mortality to affected organisms. Migratory species may be particularly susceptible as their movements may result in increased frequencies of encounters with these structures (Schilt, 2006; Poletto et al, ). Physical barriers such as small spaced louver arrays (Amaral, ; EPRI, ) and bar racks (Rosson, Kemp, & Calles, ) or screens (Gale, Zale, & Clancy, ) can potentially be used to prevent entry of aquatic organisms to intake pipes and turbines.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of earlier light apparatus is that they were typically monochromatic (e.g., white mercury vapour), constraining their effects on fishes varying in diel activity patterns and sensitivities to different colours. White lights have been used, unsuccessfully, to guide white sturgeon in the past and had limited effectiveness at reducing rates of impingement on physical barriers (Poletto et al, ). Several different light devices (Brown, ; Mueller, Neitzel, & Amidan, ; Nemeth & Anderson, ; Richards, Chipps, & Brown, ) have also been tested, although light intensity, colours, and strobing rates have been evaluated independently (Mueller et al, ; Richards et al, ; Sullivan et al, ).…”
Section: Introductionmentioning
confidence: 99%